1997
DOI: 10.1007/s004300050050
|View full text |Cite
|
Sign up to set email alerts
|

Direct sputum analysis of Pseudomonas aeruginosa macrorestriction fragment genotypes in patients with cystic fibrosis

Abstract: The distribution of bacterial populations in the airways of 13 patients with cystic fibrosis who were colonized for 6-23 years with Pseudomonas aeruginosa was investigated by genotyping of bacterial chromosomes directly isolated from 21 sputa. After removal of host material from sputum by hypotonic cell lysis and repetitive washing and centrifugation steps, agarose-embedded bacterial cells were lysed, residual eukaryotic DNA separated by field inversion gel electrophoresis, and the purified bacterial chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The presented results are consistent with those generated from previous investigations of P. aeruginosa in chronically infected CF patients [17,22,23]. These studies have all reported that, over time, most adult CF patients tend to harbour a single clone or subclone of P. aeruginosa during periods of clinical stability, and that the same bacterial clone retrieved during periods of clinical stability is also retrieved during pulmonary exacerbations [17].…”
Section: Discussionsupporting
confidence: 91%
“…The presented results are consistent with those generated from previous investigations of P. aeruginosa in chronically infected CF patients [17,22,23]. These studies have all reported that, over time, most adult CF patients tend to harbour a single clone or subclone of P. aeruginosa during periods of clinical stability, and that the same bacterial clone retrieved during periods of clinical stability is also retrieved during pulmonary exacerbations [17].…”
Section: Discussionsupporting
confidence: 91%
“…By sequencing several strains of the same clone, we now demonstrate that interclonal recombination contributes to intraclonal variation and the generation of mosaic genes. The colonized CF lung is characterized by high numbers of P. aeruginosa and only a few other bacterial competitors (Breitenstein et al, 1997). Such a scenario may facilitate the exchange of homologous genes between two or more P. aeruginosa clones.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a wide phenotypic variation has been observed in P. aeruginosa clinical isolates (Govan & Deretic, 1996;Häußler et al, 2003), despite the fact that chronically infected CF patients harbour only one or a few genotypes (Breitenstein et al, 1997) and that there seems to be no genetic or functional differences between environmental and clinical strains (Alonso et al, 1999). These observations suggest that in P. aeruginosa, phenotypic diversification would constitute a relevant survival strategy associated with pathogenesis.…”
Section: Discussionmentioning
confidence: 99%